Empirical Analysis of the Influence of Macroeconomic Factors on Stock Prices - Wang Shuoshuo (SHS Web of Conferences)
In recent years, China’s stock market has developed very rapidly, and its price fluctuations are affected by a variety of macroeconomic factors. With the deepening of economic integration, investors and government departments pay more and more attention to the transmission mechanism of monetary policy, fiscal policy, and other factors on stock market price fluctuations. In this paper, the annual data of five macroeconomic factors, namely money supply, consumer price index, exchange rate, stock turnover, and gross domestic product, are selected as samples to construct a multiple regression analysis model. The results show that the model is reconstructed after excluding the factor of GDP, and the unit root test, goodness-of-fit test, and multicollinearity test are used to test the explanatory power of the model to ensure the validity, accuracy, and interpretability of the model. Then, it analyzes the influence of the above factors on China’s stock prices, analyzes the influence mechanism based on the actual market situation, and draws relevant conclusions.